Passado e presente na construção da personagem Mwadia Malunga de O outro pé da sereia, de Mia Couto - Deramio, Brígida Priscila Neves (2025)
This master's thesis aims to analyze the process of constructing memory and remembering the characters in O outro pé da sereia (2006), with the main focus being the protagonist, Mwadia Malunga. To this end, it must be taken into account that the effects of meaning found in the narrative are obtained through combinations and the exploration of the meanings of words and the author's peculiar style, resulting in unique writing. The arrangement of the novel's chapters presents a logical construction of the characters and a correlation between different times. In the Coutian narrative it is clear that the notion of time goes beyond the chronological, it extends to something immaterial, a factor that directs us to the issue of identity, including that which refers to the concept of death. Therefore, this study will demonstrate that memory structures the relationships diagnosed in the aforementioned work and in the perspectives to be worked on within Portuguese-speaking African literature. The research will be developed through reading and analysis of the novel and theoretical works that evaluate it, such as Aleida Assmann, Maurice Halbwachs, Paul Ricoeur and Márcio Seligmann-Silva, mainly.